Design of Meteor and Ionospheric Irregularity Observation System and First Results. Issue 4 (22nd April 2022) - Li, Guozhu; Xie, Haiyong; Wang, Ye; Yang, Sipeng; Hu, Lianhuan; Sun, Wenjie; Wu, Zhi; Ning, Baiqi; Li, Yi; Zhao, Xiukuan; Reid, Iain M.; Yu, You
Abstract: The Meteor and ionospheric Irregularity Observation System (MIOS), which consists of multi‐station optical subsystem at Ledong (18.4°N, 109°E) and Sanya (18.3°N, 109.6°E), and radar subsystem including a 38.9 MHz all‐sky interferometric radar and a 47.5 MHz coherent phased array radar at Ledong, has been in full operational since December 2021. This paper describes the system design and first results of meteor plasma density irregularities and corresponding meteoroids. The MIOS optical subsystem consists of a few tens of video cameras for observing optical meteor trail and spectrum. The MIOS phased array is composed of 135 Yagi antennas, arranged in sword‐like grid and grouped into 15 identical subarrays, with distances separated by 2–19.5 times the wavelength for unambiguous interferometry measurements. The phased array can form narrow and wide beams, with half power width of 8° and 24° in azimuth, respectively, allowing narrow‐beam pulse‐to‐pulse steering and wide‐beam multi‐baseline imaging observations in the east‐west direction. Observational results show that the MIOS is capable of unambiguously locating various meteor echoes, that is, head, specular and non‐specular echoes, revealing the structural evolution of field‐aligned and non‐field‐aligned irregularity, and of determining the properties of meteoroids producing/not producing irregularities. Cases of bright meteors producing non‐field‐aligned irregularities and not producing field‐aligned irregularities respectively are presented, and possible factors affecting the generation of meteor trail irregularities are discussed based on current understanding. It is expected that the MIOS will provide an important tool to study the generation and evolution of various meteor trail irregularities and the properties of the corresponding meteoroids. Plain Language Summary: Meteoroids entering the Earth's atmosphere significantly disturb the background ionosphere, producing ionized columns and plasma density irregularities, change the ionospheric composition, and even seed large‐scale ionospheric irregularity structures. However, due to the limitations of previous measurements, some physical processes, for example, how efficiently various meteoroids affect the background ionosphere, either producing or not producing some specific meteor trail irregularity phenomena, and the related meteoroid properties and origins, are less well understood. This calls for a facility to measure the properties of both the meteor trail and its corresponding meteoroid, and thus to reveal potential factors affecting the generation of meteor trail irregularities and the disturbance of the background ionosphere. Under the support of national natural science foundation of China, a Meteor and ionospheric Irregularity Observation System (MIOS) was designed to simultaneously capture the radar and optical signatures of meteors and plasma density irregularities. Here we report the initial measurements of the MIOS, which demonstrate its capabilities for observing various meteor and irregularity phenomena. Key Points: An optical and radar facility (MIOS) intended to study how meteoroids change the Earth's background ionosphere has been developed First observations of field‐ and non field‐aligned meteor irregularities and the corresponding meteoroids from the facility are presented The facility is expected to play an important role in the study of various meteors, their origin and possible processes affecting ionosphere